2016
DOI: 10.3390/ijerph13060537
|View full text |Cite
|
Sign up to set email alerts
|

Residential Risk Factors for Atopic Dermatitis in 3- to 6-Year Old Children: A Cross-Sectional Study in Shanghai, China

Abstract: Background: Atopic dermatitis (AD) is common among pre-school children in Shanghai. This study aimed to identify the risk factors for childhood AD from the perspectives of home environment, demographics and parents-grandparents’ atopic disease. Methods: A cross-sectional study was conducted in Shanghai in April–June, 2010. Preschool children’s parents or guardians were invited to participate a questionnaire survey in six districts (two urban and four suburban/rural) and 6624 children were finally recruited (51… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 24 publications
1
10
1
3
Order By: Relevance
“…This is probably a result of the small sample size of participants in our study reporting the presence of animals in the household. We also failed to show a statistically significant difference in the prevalence of ARDs between participants in urban versus rural areas, which can be contrasted with previous reports showing that urbanization of an area is associated with increased prevalence of respiratory allergic disease [ 35 , 36 ]. One large scale study of almost 10,000 participants conducted in Mongolia found an increasing rate of sensitization between different levels of urbanization—from 13.6% in villages, 25.3% in rural towns, to 31.0% in the city—giving strong evidence that economic development is directly tied rates of allergic disorders [ 37 ].…”
Section: Discussioncontrasting
confidence: 99%
“…This is probably a result of the small sample size of participants in our study reporting the presence of animals in the household. We also failed to show a statistically significant difference in the prevalence of ARDs between participants in urban versus rural areas, which can be contrasted with previous reports showing that urbanization of an area is associated with increased prevalence of respiratory allergic disease [ 35 , 36 ]. One large scale study of almost 10,000 participants conducted in Mongolia found an increasing rate of sensitization between different levels of urbanization—from 13.6% in villages, 25.3% in rural towns, to 31.0% in the city—giving strong evidence that economic development is directly tied rates of allergic disorders [ 37 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, home renovation activities including buying new furniture and home painting, and the use of synthetic, modernised flooring and wall materials emit chemicals including volatile organic compounds (VOCs) which may trigger AD. 37 , 40 , 41 Further, the influence of indoor factors was reported to begin as early as during pregnancy. For instance, the pooled OR for home renovation during pregnancy was 1.39 (95% CI, 1.26–1.53; I 2 = 0.6%, p = 0.402).…”
Section: Resultsmentioning
confidence: 99%
“…Use of topical emollients during the neonatal period has been shown to decrease the risk of AD in Japanese infants . Allergy to dust mites, intranatal exposure to a newly renovated or decorated house, and high levels of household mould may play a role in Chinese children and adults . In Taiwan, people born in October through December are more likely to develop AD …”
Section: Aetiology and Genetics Of Atopic Dermatitis In Non‐european mentioning
confidence: 99%